Seasonal Variation of Trauma in Western Massachusetts: Fact or Folklore?. Issue 1 (7th September 2017) - Nahmias, Jeffry; Poola, Shiva; Doben, Andrew; Garb, Jane; Gross, Ronald I
Abstract : Background: Previous studies have demonstrated a significant relationship between weather or seasons and total trauma admissions. We hypothesized that specific mechanisms such as penetrating trauma, motor vehicle crashes, and motorcycle crashes (MCCs) occur more commonly during the summer, while more falls and suicide attempts during winter. Methods: A retrospective review of trauma admissions to a single Level I trauma center in Springfield, Massachusetts from 01/2010 through 12/2015 was performed. Basic demographics including age, Injury Severity Score (ISS), and length of stay were collected. Linear regression analysis was used to test the association between monthly admission rates and season, year, injury class, and mechanism of injury, and whether seasonal variation trends were different according to injury class or mechanism. Results: A total of 8886 admissions had a mean age of 44.6 and mean ISS of 11.9. Regression analysis showed significant seasonal variation in blunt compared with penetrating trauma (p<0.001), MCC (p<0.001), and falls (p=0.002). In addition, seasonal variation differed according to injury class or mechanism. There were significantly lower rates of MCCs in winter compared with all other seasons and conversely higher rates of total falls in winter compared with other seasons. Discussion: A significant seasonal variation in blunt trauma, MCC, and falls was observed. This has potential ramifications for resource allocation, including trauma prevention programs geared toward mechanisms of injury with significant seasonal variation. Level of evidence: Retrospective Review, Level IV.